2022
DOI: 10.1021/acschemneuro.2c00539
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Adoptive Cellular Therapy-Based Vaccine in a Transgenic Mouse Model of α-synucleinopathy

Abstract: Aggregated α-synuclein, a major constituent of Lewy bodies plays a crucial role in the pathogenesis of α-synucleinopathies (SPs) such as Parkinson's disease (PD). PD is affected by the innate and adaptive arms of the immune system, and recently both active and passive immunotherapies targeted against α-synuclein (α-syn) are being developed and show promise as novel treatment strategies for such diseases. Specifically, dendritic cell-based vaccines have shown to be an effective treatment for SPs. Here, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Recent studies have shown the potential of neuroimaging techniques for examining brain-correlates of aSyn toxicity in animal models (Chu et al, 2020(Chu et al, , 2022Lackie et al, 2022); namely, Chu et al ( 2020) provides preliminary evidence for diffusion and functional MRI markers linked to the progression of aSyn pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown the potential of neuroimaging techniques for examining brain-correlates of aSyn toxicity in animal models (Chu et al, 2020(Chu et al, , 2022Lackie et al, 2022); namely, Chu et al ( 2020) provides preliminary evidence for diffusion and functional MRI markers linked to the progression of aSyn pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the potential of neuroimaging techniques for examining brain‐correlates of aSyn toxicity in animal models (Chu et al, 2020, 2022; Lackie et al, 2022); namely, Chu et al (2020) provides preliminary evidence for diffusion and functional MRI markers linked to the progression of aSyn pathology. In terms of structural MRI, a common modality acquired in clinical research to examine the brain morphology and signs of atrophy and neurodegeneration in human patients, our group has examined neuroanatomy using structural MRI in the M83 homozygous mouse model, which however does not provide information on seed‐initiation of pathology as PFF‐injected mice (Lackie et al, 2022).…”
Section: Discussionmentioning
confidence: 99%